2011
DOI: 10.1002/app.34297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SiO2 and Al2O3 nanofillers on polyethylene properties

Abstract: Polymers filled with inorganic nanoparticles have become interesting materials as dielectrics because of their improved mechanical and electrical properties compared with the unfilled polymers and with polymer microcomposites. These improvements are mainly due to the large surface area of nanoparticles and new polymer-nanofiller interface characteristics. In the present work, polyethylene nanocomposites with SiO 2 and Al 2 O 3 nanoparticles were prepared by melt mixing. Mechanical and electrical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 55 publications
7
36
0
1
Order By: Relevance
“…Modest improvements in tensile strengths (6% at 2 wt% C-GNPs, and 5% at 1 wt% M-GNPs) were observed with the addition of low fractions of GNPs. This improvement with small amounts of additives was also reported by Panaitescu et al 34 who studied ~2 wt% …”
Section: Tensile Strengthsupporting
confidence: 61%
“…Modest improvements in tensile strengths (6% at 2 wt% C-GNPs, and 5% at 1 wt% M-GNPs) were observed with the addition of low fractions of GNPs. This improvement with small amounts of additives was also reported by Panaitescu et al 34 who studied ~2 wt% …”
Section: Tensile Strengthsupporting
confidence: 61%
“…Study HDPE and Al 2 O 3 PNC assessed the influence of adding inorganic Al 2 O 3 and SiO 2 fillers on their electrical and mechanical properties and they concluded the addition of fillers significantly altered nanocomposite morphology. In this study, better dielectric and mechanical properties were obtained in nanocomposites with 2% of Al 2 O 3 . Similar results were obtained with LDPE/Al 2 O 3 PNC and was found that nanoparticles can act as nucleating agents, promoting morphological changes, particularly in the crystalline structure of the PNC, as well as the configuration and distribution of free charges, which increases the dielectric breakdown of the materials .…”
Section: Introductionsupporting
confidence: 84%
“…On the basis of the comparison between 2 and 8 vol % Al 2 O 3 , TiO 2 , and organoclay‐filled PP/EPDM nanocomposites, the dielectric constant increased with increasing addition of nanofiller particles. The enhancement of dielectric constant values for 8 vol % Al 2 O 3 , TiO 2 , and organoclay in PP/EPDM nanocomposties compared with unfilled PP/EPDM and 2 vol % nanofiller in their respective systems is probably due to the significant contribution of the interfacial polarization, which is determined by the increased number of charges (impurities and small ions) introduced in the polymer by the nanoparticles . PP/EPDM/TiO 2 had the highest dielectric constant, followed by PP/EPDM/Al 2 O 3 and PP/EPDM/organoclay.…”
Section: Resultsmentioning
confidence: 98%